Measurement of ion stopping power in the framework of nuclear reactions in plasmas - Trifirò, Antonio; Altana, Carmen; Bortot, Davide; Cirrone, Pablo; Consoli, Fabrizio; De Luca, Saverio; De Angelis, Roberto; Cavallaro, Salvatore; Ciampi, Caterina; Lanzalone, Gaetano; Malferrari, Luciana; Mazzucconi, Davide; et al. (HNPS Advances in Nuclear Physics, 2025)
The study of nuclear reactions and interactions in plasmas has recently assumed great importance because of its connection with processes such as laser-driven ion acceleration and nuclear fusion for massive energy production. In fact, the extremely high electron densities established in the plasma bring to different behaviour of charged particles with respect to that observed when a stable beam impinges on a solid target. Ion stopping power in cold matter is relatively well known and has been characterized with the help of a large set of experimental data and theoretical studies; on the contrary a lot of open questions remain when it comes to ions stopping in a plasma, especially in the energy domain where the projectile ion velocity approaches that of free plasma electrons. The main aim of this work is a systematic and careful measurement of stopping power for several ions versus plasma parameters, especially in the region of thermal velocities, where the energy deposition should depend strongly on plasma temperature, density and ionization fraction. The plasma will be generated under vacuum, by interaction of a laser beam with a solid target. Plasma plume will be characterized in temperature and density by optical and X-ray diagnostics; simultaneously the energy loss will be measured for an ion microbeam crossing the plume. This contribution provides an overview of the experimental technique and the results obtained during first tests for the characterization of experimental apparatus.